Sick-building syndrome - Sotiriadou, K.; Dallas, D.; Stavrakakis, P.; Chalaris, Michail; Sarafis, Pavlos (My University, 2010)
In the present article we study, from theoretical point of view, the sick-building syndrome (SBS). We analyse more than 50 symptoms that are reported by those who suffer from the SBS. In addition, the most important factors that lead to the development of SBS are distinguished and we mention the substances that generally seem to cause SBS. Moreover, a model about the prediction and ascertainment of SBS has been proposed. Finally, overall rules for prevention and confrontation of this problem are suggested.
Keywords: Sick-building syndrome; Symptoms; Indoor environmental quality; Workplace environment; Health hazard evaluations